SYNTHESIS AND POLYMERIZATION OF N-(TERT-BUTYLOXYCARBONYL)MALEIMIDE AND FACILE DEPROTECTION OF POLYMER SIDE-CHAIN T-BOC GROUPS - AHN, KD; LEE, YH; KOO, DI (ELSEVIER SCI LTD, 1992)
A new t-BOC protected monomer, N-(tert-butyloxycarbonyl)maleimide (t-BOCMI) 3 was synthesized by thermolysis in a high yield and a new kind of t-BOC protected polymer was prepared by radical copolymerization. t-BOCMI and styrene derivatives (X-St) were readily copolymerized to obtain alternating copolymers of P(t-BOCMI/X-St) 5 in high conversions. The t-BOCMI units of the t-BOC protected copolymers were converted to the maleimide (MI) units by heating at about 150-degrees-C or above, releasing 2-methylpropene and carbon dioxide. The facile deprotection of the side-chain t-BOC groups from the protected copolymers was attained to bring about a large polarity change. The deprotected copolymers P(MI/Y-St) 6 have very high glass transition temperatures (T(g)s) of about 250-degrees-C and good solubility in aqueous base solutions, whereas the t-BOC polymers P(t-BOCMI//X-St) are only soluble in organic solvents. The t-BOC protected maleimide polymers were found to have specific properties for application as chemically amplified resist materials such as alkaline solubility, high T(g) and facile deprotection.
Keywords: COPOLYMERS; RESISTS; DESIGN